Chitooligosaccharide guanidine inhibits high glucose-induced activation of DAG/PKC pathway by regulating expression of GLUT2 in type 2 diabetic nephropathy rats. (February 2018) - Zhang, Hai; Zhang, Shengsheng; Wang, Li; Liu, Xiaofei; Wu, Yuntang
Graphical abstract: COSG may inhibit high glucose-induced activation of DAG/PKC pathway by regulating expression of GLUT2 and exert certain nephro-protection in early stage of experimental DN in rats. Highlights: COSG is shown to attenuate blood glucose in diabetic nephropathy rats. COSG attenuates blood glucose in diabetic nephropathy rats by downregulating GLUT2 in kidney. COSG inhibits the activity of DAG/PKC pathway. Abstract: Previous results from our laboratory showed that chitosan biguanidine hydrochloride (CSGH) and chitooligosaccharide guanidine (COSG) could control glucose uptake by regulating the expression of glucose transporters (GLUTs) in vitro experiments. In this study, we try to delineate changes observed in activation of diacylglycerol (DAG)/protein kinase C- β (PKC- β ) pathway and GLUT2 in kidney. STZ-induced diabetic rats were administered COSG via daily intra-gastric gavage for 8 weeks. Obviously, COSG significantly attenuated fasting blood glucose and blood glucose level by modulating the over-expression of GLUT2 and the level of DAG as well. Immunohistological examination revealed that factors such as PKC- β and transforming growth factor- β (TGF- β ) diminished to various extents after treatment with COSG, which impinged on the synthesis of extracellular matrix (ECM) components like fibronectin (FN). As a result, high glucose-induced activation of DAG/PKC pathway is inhibited, which is associated with the concentration of glucose controlled by the expression of GLUT2 with the treatment of COSG.